Making charts - Rooney, Anne (London, 2005)
Making charts teaches you all the skills you need to create charts. You'll learn how to gather information, input data to a chart on your computer, check your work and make your chart look amazing
Keywords: Charts, diagrams, etc; Children's nonfiction; Computers Study and teaching (Primary) Juvenile